THE SYSTEMATIC REVIEW OPEN SURGERY VS MINIMALLY INVASIVE IN HIGH RISK ENDOMETRIAL CANCER - Supriyadi, Agung; Andimapali, Zulfikar; Fitria, Adina; Whisnu Dewanegara, Rahadiyan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: When treated with minimally invasive surgery (MIS), women with early-stage endometrial cancer recover more quickly from surgery than when they have open operations; nevertheless, there is no discernible difference in terms of overall survival or progression-free survival. Aims : This systematic review is to review the comparison of open surgery and minimally invasive in high risk endometrial cancerMethods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 144 articles, whereas the results of our search on SCIENCE DIRECT brought up 588 articles. The results of the search conducted for the last year of 2014 yielded a total 121 articles for PubMed and 175 articles for SCIENCE DIRECT. In the end, we compiled a total of 5 papers, 4 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included five research that met the criteria.Conclusion: In summary, this systematic review of observational studies showed that the prognosis of endometrial cancer patients with high risk histology was unaffected by minimally invasive surgery and might confirm the findings of this rare but lethal malignancy.